The Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker of Fournier’s Gangrene Severity: A Meta-Analysis - Konstantinos Seretis; Nikolaos Bounas; Konstantinos Sfaelos; Georgios Gaitanis; Ioannis Bassukas (Infectious Disease Reports)
Background/Objectives: Fournier’s Gangrene (FG) is a severe and potentially fatal necrotizing infection of the perianal and genital regions, which necessitates prompt therapeutic interventions to prevent disease progression. Accruing evidence from recent research indicates that the neutrophil‒to-lymphocyte ratio (NLR) can predict clinical severity and mortality risk in patients with critical illnesses across various etiologies. This meta-analysis aimed to assess the efficacy of NLR as a prognostic indicator for mortality in patients with FG. Methods: An electronic literature search was conducted across several databases from their inception to 31 May 2024, following a predetermined protocol. Study quality was evaluated using the Cochrane risk of bias tool. A random-effect model was utilized to synthesize the available data. Results: Twelve studies reporting on 767 patients were included in the meta-analysis. Higher NLR levels at presentation were recorded in non-survivors than in survivors (MD = 4.49 [95% CI: 0.67–8.32]; p = 0.02). A 76% increased mortality risk was detected for patients with an NLR ≥ 8 (1.76 RR [1.35–2.3], p = 0.0001), and the mortality risk was more than twofold greater for patients with an NLR ≥ 10 compared to the remaining patients (RR = 2.31 [1.27–4.21], p = 0.006). All included studies exhibited a moderate to serious risk of bias. Conclusions: This meta-analysis reveals that the NLR represents a promising biomarker that can serve as a prognostic indicator in patients with FG. Future studies should address the establishment of proper disease-specific cutoff values to aid in clinical decision-making.